2010
DOI: 10.1111/j.1742-4658.2010.07564.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of amyloid‐β‐related pathologies in Alzheimer’s disease

Abstract: In the early 1990s, breakthrough discoveries on the genetics of Alzheimer’s disease led to the identification of missense mutations in the amyloid‐β precursor protein gene. Research findings quickly followed, giving insights into molecular pathogenesis and possibilities for the development of new types of animal models. The complete toolbox of transgenic techniques, including pronuclear oocyte injection and homologous recombination, has been applied in the Alzheimer’s disease field, to produce overexpressors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 164 publications
(191 reference statements)
0
89
0
2
Order By: Relevance
“…Familial AD is linked to inherited mutations in AD-related genes and represents a small percentage of AD cases, whereas sporadic AD represents the vast majority of cases and is not inherited. Results from transgenic mice bearing mutations in APP, PSEN1/2, and TAU show synaptic dysfunction in early stages of AD, before overt neurodegeneration (2,3). More recent studies have demonstrated a critical role for soluble Aβ oligomers as an early trigger for AD, as well as associations with memory and neural plasticity loss (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Familial AD is linked to inherited mutations in AD-related genes and represents a small percentage of AD cases, whereas sporadic AD represents the vast majority of cases and is not inherited. Results from transgenic mice bearing mutations in APP, PSEN1/2, and TAU show synaptic dysfunction in early stages of AD, before overt neurodegeneration (2,3). More recent studies have demonstrated a critical role for soluble Aβ oligomers as an early trigger for AD, as well as associations with memory and neural plasticity loss (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…However, partial reproduction of AD neuropathology and cognitive deficits has been achieved with various approaches (20,21). Mouse models have been established that express identified human mutations that give rise to these pathological hallmarks of AD (19,(21)(22)(23). Despite their undoubted value, the transgenic Q.L.…”
Section: Discussionmentioning
confidence: 99%
“…4 Inflammatory factors have been further implicated in cognitive impairment and dementia using mouse models. 5 These include transgenic animals in which chemoattractant proteins or receptors such as Ccl2 or Ccr2 have been abolished. 5 These genes, associated with the migration of phagocytic and inflammatory macrophages, have been associated with Alzheimer pathology and peripheral atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…5 These include transgenic animals in which chemoattractant proteins or receptors such as Ccl2 or Ccr2 have been abolished. 5 These genes, associated with the migration of phagocytic and inflammatory macrophages, have been associated with Alzheimer pathology and peripheral atherosclerosis. [5][6][7] Ccr2-deficient mice show early accumulation of b-amyloid, with premature mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation